The Detection of the Escherichia coli Gene in Well Water in Bojonegoro Using Polymerase Chain Reaction (PCR) - Prayekti, Endah; Rosiana Dewi Regita; Khiliah Navis (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
ABSTRACT Escherichia coli (E. coli) is an indicator of water contamination that can be pathogenic, especially the Enterotoxigenic E. coli (ETEC) pathotype, which carries the heat-resistant enterotoxin (est) gene. Well water that does not meet clean water quality standards can become a medium for Escherichia coli contamination, so it is important to perform molecular genetic detection. The study aimed to determine the presence of Escherichia coli bacteria and detect the est gene from well water isolates using the Polymerase Chain Reaction (PCR) method. Samples were collected from 19 wells using purposive sampling techniques. Escherichia coli identification was performed through conventional isolation, Gram staining, biochemical tests, and culture on selective media (EMB and MCA). The results of this study showed that four samples tested positive for Escherichia coli. Molecular detection using PCR for the est gene in Escherichia coli was not detected in any of the four Escherichia coli isolates. Based on these results, it was concluded that Escherichia coli was present in the samples, but the est gene was not detected. Keywords: Escherichia coli, est gene, well water, PCR ABSTRAK Escherichia coli (E. coli) merupakan indikator pencemaran air yang dapat bersifat patogen, terutama patotipe Enterotoxigenic E. coli (ETEC) yang membawa gen enterotoksin tahan panas (est). Air sumur yang tidak memenuhi standar kualitas air bersih dapat menjadi media kontaminasi Escherichia coli, sehingga penting dilakukan deteksi genetik secara molekuler. Penelitian bertujuan untuk mengetahui keberadaan bakteri Escherichia coli dan mendeteksi gen est dari isolat air sumur menggunakan metode Polymerase Chain Reaction (PCR). Sampel diambil dari 19 sumur menggunakan teknik purposive sampling. Identifikasi Escherichia coli dilakukan melalui isolasi konvensional, pewarnaan Gram, uji biokimia, dan kultur pada media selektif (EMB dan MCA). Hasil penelitian ini menunjukkan adanaya 4 sampel yang memiliki positif Escherichia coli. Deteksi molekuler dengan PCR terhadap gen est pada Escherichia coli tidak ditemukan pada keempat isolat Escherichia coli. Berdasarkan hasil penelitian ini disimpulkan bahwa pada sampel ditemukan Escherichia coli tetapi tidak ditemukan gen est. Kata Kunci: Escherichia coli, gen est, air sumur, PCR